2022
DOI: 10.1111/aos.15116
|View full text |Cite
|
Sign up to set email alerts
|

Refractive error, accommodation and lens opacification in adults born preterm and full‐term: Results from the Gutenberg Prematurity Eye Study (GPES)

Abstract: Purpose: To evaluate the long-term effects of different degrees of prematurity, retinopathy of prematurity (ROP) and associated perinatal factors on refractive error, accommodation and lens opacification development in adults born preterm aged 18-52 years. Methods: The Gutenberg Prematurity Eye Study (GPES) investigated adults born preterm and full-term at 18-52 years in Germany to assess refractive error, accommodation amplitude and lens opacification. The participants were grouped into normal gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
15
0
2
Order By: Relevance
“…For the GPES, every preterm newborn with a GA ≤ 32 weeks and every second randomly chosen preterm newborn with GA 33–36 weeks was contacted and invited to participate. From each month from 1969 to 2002, 6 (3 males and 3 females) randomly selected full-term subjects with a birth weight between the 10th and 90th percentile were also invited to serve as controls as reported earlier [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the GPES, every preterm newborn with a GA ≤ 32 weeks and every second randomly chosen preterm newborn with GA 33–36 weeks was contacted and invited to participate. From each month from 1969 to 2002, 6 (3 males and 3 females) randomly selected full-term subjects with a birth weight between the 10th and 90th percentile were also invited to serve as controls as reported earlier [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…From each month from 1969 to 2002, six (3 males and 3 females) randomly selected full‐term subjects with a birth weight between the 10th and 90th percentile were also invited to serve as controls. The study examinations were performed between 2019 and 2021 as reported earlier 27‐35 . The flow chart for eligibility and effective recruitment efficacy proportion is displayed in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…The study examinations were performed between 2019 and 2021 as reported earlier. [27][28][29][30][31][32][33][34][35] The flow chart for eligibility and effective recruitment efficacy proportion is displayed in Figure S1. Each recruited participant underwent a detailed ophthalmological examination including Scheimpflug imaging, ocular biometry and a medical history interview.…”
Section: Study Populationmentioning
confidence: 99%
“…Die Proband*innenrekrutierung und der Selektionsalgorithmus sind in Abb. 1S (Zusatzmaterial) sowie an anderer Stelle beschrieben 23 , 24 , 25 , 26 , 27 , 28 , 29 . Alle Teilnehmenden wurden einer detaillierten und umfassenden augenärztlichen Untersuchung unterzogen, einschließlich einer Untersuchung der Refraktionsfehler und einer Befragung zur Krankengeschichte.…”
Section: Patienten/materials Und Methodenunclassified